Endophytic Bacillus bacteria with RNase activity in the resistance of potato plants to viruses - G. F. Burkhanova; A. V. Sorokan; E. A. Cherepanova; E. R. Sarvarova; R. M. Khairullin; I. V. Maksimov (Вавиловский журнал генетики и селекции)
Viral diseases annually cause significant crop losses and significantly reduce the quality of products, including potatoes, some of the most important crops. Currently, viruses cannot be controlled with chemical pesticides, since known antiviral compounds are teratogenic and hazardous to people’s health. Biocontrol agents based on endophytic microorganisms may be an alternative to them. Many strains of Bacillus produce ribonucleases (RNases). Our laboratory possesses a collection of bacteria that produce various metabolites and have RNase activity. The results showed that the inoculation of potato with B. subtilis 26D and B. thuringiensis increased the grain yield by 32–43 %. In addition, the treatment of potato plants with Bacillus spp. significantly reduced the infection of potato plants with virus M. The prevalence of the disease in potato plants was significantly reduced from 60 % in the control to 18 % (B. subtillis 26D) and 25–33 % (B. thuringiensis) in the inoculated plants. Similarly, the infection index decreased from 14 in the control to 1 in the inoculated plants. The further study of molecular mechanisms related to bacterial induction of plant defense reactions in response to viral infections will lead to a better understanding of stress resistance problems. The endophytic microorganisms studied in this report may become the basis for the creation of biological agents for plant protection.